Kacey Cruz: capstone - Cruz, Kacey, artist (Colorado State University. Libraries, 2026)
The artist's statement: The reason why I built this is because there are not many artworks that have different kinds of art styles in them like drawing, with painting etc. Also, another reason why I did this artwork is because of how I think it is cool that we don't see much artwork being built like this. Like how these beavers are building this scene while our eyes are the camera in this artwork. Art can be all messed up because it is fun, and art does not need to be fancy or normal, it can be weird and fun and no matter what, just do what you like to do. The reason why I wanted to make this artwork is because I like how parrots look. I wanted to make this artwork very colorful and unique. I wanted to make this artwork pop out by how it looked surrounded by plants and how I made the feathers out of paper. I think this artwork teaches how colors and the use of paper can make a picture pop. This artwork was fun to make, and I really used my imagination while making it. Another reason I made this is because of a mighty bird named Parker that had a love triangle. But was murdered by his love Paige. The reason why I made this artwork is because of what it means and what it means for Halloween. This artwork has a lot of meanings like having fun, being scared, being cool, and a lot of other things. The reason why I made this artwork is because I made the raccoons had the name yin and yang because how it connected to Halloween and pumpkins a bit because the pumpkins color is red, yellow and how these two colors connect with yin and yang. The reason for yin being with red is that they both show darkness like yin is dark, earth and red shows death and madness. While for yang being with yellow is that they both show light because yang is light, heaven and yellow is life and happy. That is why I made the pumpkins the raccoons be this because to show what Halloween is because Halloween can be about death, life, darkness, happy or mad too, so Halloween can be anything like how these raccoons show it. It does not matter if you are small or tall, scared or brave, the same or different, you can always have hope and dreams, and don't ever stop trying to achieve your goals.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: drawing